Amide synthesis from alcohols and amines catalyzed by a RuII–N-heterocyclic carbene (NHC)–carbonyl complex - Saha, Biswajit; Sengupta, Gargi; Sarbajna, Abir; Dutta, Indranil; Bera, Jitendra K. (Journal of organometallic chemistry, 2014)
Treatment of [Ru2(CO)4(CH3CN)6](BF4)2 with 3-methyl-1-(pyridin-2-yl)-imidazolium bromide in the presence of tetrabutylammonium bromide at room temperature in dichloromethane affords a RuII–N-heterocyclic carbene–carbonyl complex [Ru(py-NHC)(CO)2Br2] (1). Catalyst 1 displays diverse substrate scope for phosphine-free acceptorless coupling between alcohols and amines to amides at low catalyst loading. A RuII-dihydride/Ru0 sequence is proposed in the catalytic cycle. Ru(II) catalyst catalyzes phosphine-free acceptor-less coupling between alcohols and amines to amides at low catalyst loading. [Display omitted] •Oxidative route to Ru–N-heterocyclic carbene complex from metal–metal bonded precursor.•Catalyst for direct amidation from alcohols and amines.•Phosphine-free, acceptorless amidation catalyst at low catalyst loading.•A RuII-dihydride/Ru0 sequence is proposed in the catalytic cycle.